2018
DOI: 10.1002/hpm.2539
|View full text |Cite
|
Sign up to set email alerts
|

Measuring inequalities in the demographical and geographical distribution of physicians in China: Generalist versus specialist

Abstract: The present study compares the distribution inequalities between generalist and specialist physicians in China for the first time. Despite the rapid increase in quantity and density of these physicians, the whole nation faces a severe shortage and maldistribution of generalist physicians. The increase in the number of physicians has not necessarily eliminated the geographical distribution inequalities. The government should consider all influencing factors when allocating health workers and continue promoting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…It is an inequality measure without considering the spatial distribution of data. A previous study reported that the Gini coefficients for physicians by population and by area across the 31 provinces of China were 0.2 and 0.7, respectively; thus, we calculated the coefficients using Shenzhen data [36].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an inequality measure without considering the spatial distribution of data. A previous study reported that the Gini coefficients for physicians by population and by area across the 31 provinces of China were 0.2 and 0.7, respectively; thus, we calculated the coefficients using Shenzhen data [36].…”
Section: Methodsmentioning
confidence: 99%
“…X i represents the cumulative proportion of i population or area and Y i represents the corresponding cumulative proportion of medical resources. Gini coefficients were calculated using the formula below; a Gini coefficient of 0 expresses perfect equality, while a value of 1 indicates maximal inequality [36]. G=1i=0n1(Yi+1+Yi)(Xi+1Xi)…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, they need to respond to the general public, which is why they also invest heavily in public health care, especially primary care. 54,55 Our regression results demonstrate that the local population is an important determinant behind the regional distribution of NTH, TH and GATH. Without a significant increase in the general public's health benefits, the government could hardly claim the legitimacy of the communist party's ruling.…”
Section: Reasoningmentioning
confidence: 69%
“…With the Gini coefficient as an indicator of distribution inequity, China has a severe geographical disparity in physicians (a Gini coefficient higher than 0.6), and this trend is worsening (9,10). The distribution of licensed physicians by age warrants attention as well ( Figure 2B).…”
Section: Supply Of Physiciansmentioning
confidence: 99%